2021
DOI: 10.4162/nrp.2021.15.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptance of edible insect foods: an application of the extended theory of planned behavior

Abstract: BACKGROUND/OBJECTIVES The purpose of this study was to measure consumer acceptance of edible insect foods (EIFs) while applying the extended theory of planned behavior (ETPB). Insects as food have attracted interest as potential possible sources of nutrition for the future. This study investigated consumers' perception toward insect food and future purchase behaviors. SUBJECTS/METHODS A survey was conducted among citizens of Korea. About two thirds of respondents had tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Of various theories in the consumer behavior, the superior prediction power of the TPB in explaining individuals’ behavior is properly documented in various settings [ 14 , 28 , 53 ]. The current research adopted the TPB and it successfully validated the applicability of the TPB in comprehending individuals’ intention formation to visit edible insect restaurants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of various theories in the consumer behavior, the superior prediction power of the TPB in explaining individuals’ behavior is properly documented in various settings [ 14 , 28 , 53 ]. The current research adopted the TPB and it successfully validated the applicability of the TPB in comprehending individuals’ intention formation to visit edible insect restaurants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang et al [ 27 ] conducted a case study in examining driving forces of travelers’ pro-environmental behavior and their results showed that subjective norm increased behavioral intentions. Bae and Choi [ 14 ] built their research framework on a basis of the TPB and their analysis using 392 Korean citizens’ responses and discovered the significant impact of subjective norm on individuals’ behavioral intentions toward edible insects. More specifically, they asserted that if a person’s significant others intake edible insects as regular food ingredients, then the individual will follow such behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it is important to point out that generally, in the Theory of Planned Behaviour (TPB), is explained how, positively or negatively, the personal feeling towards the subject (e.g., Neophobia) influence the purchase intention as well as influence the Intrinsic perceived Quality of fruits and food products (Kim et al, 2014;Ting et al, 2016). Hence, TPB is an extended theory of TRA in which was added the element of perceived Intrinsic Quality by personal human feelings (Bae et al, 2021) Thus, on the basis of these two theories, the food Neophobia along with the Country Of Imagine and perceived Quality might strongly influence the Behavioural Intention (Garrido et al, 2021;Espejel and Fandos, 2009b), as we hypnotize in this study putting together the two theories.…”
Section: Neophobiamentioning
confidence: 96%